Implementation of Coding Theory with The Extended Hamming Code in Steganography - Jannah, Nurul; Hamid, Nur (IAIN Kediri, 2023)
Data security needs to be considered to avoid noise when sending data or data breaches by hackers. In this article, we implement data security using a combination of coding theory and steganography. The code used is an extended Hamming code [8.4]. The media used is a grayscale image of size of lengths 50,100,150,200,250 and 300 characters with 6 attempts. In addition, we show the PSNR result obtained and also the computation time.